Scale Insects and Mealybugs on Ornamental Plants - Eileen A. Buss; Jay Cee Turner (EDIS)
Revised! ENY-323, a 6-page illustrated fact sheet by Eileen A. Buss and Jay Cee Turner, describes this group of serious pests of many ornamental plants. Includes sections on biology and behavior; armored scales, soft scales, mealybugs and sooty mold; detecting infestations; and cultural, biological, and chemical control; and tables listing pesticides available for professional use on ornamentals. This revision includes an additional table of pesticides available for use by homeowners. Part of the Master Gardener Handbook. First published by the UF Department of Entomology and Nematology, October 1993, revised June 2006.